Pengaturan Kampanye di Media Sosial: Telaah Kritis Peraturan KPU No 15 Tahun 2023 Tentang Kampanye Pemilihan Umum - Sapardiyono Sapardiyono; Galih Bagas Soesilo (Jurnal Interpretasi Hukum, 2024)
Campaigning in the digital age is increasingly facilitated by various features that support creativity and speed in sharing information about the campaign interests of election candidates. Social media has become a significant platform for influencing public opinion and shaping political narratives. Campaign arrangements in social media have been regulated in the provisions of articles 38 of KPU Regulation No. 15 of 2023. This study is intended to determine the extent of regulation of campaigns on social media in the 2024 elections and to predict various problems that may arise. The research method used is normative juridical. At the same time, the data used is secondary data, consisting of primary legal materials and secondary legal materials. The results reveal that the word ‘Social Media’ appears and is mentioned in this KPU Regulation 62 times. However, the existing KPU Regulation has not fully accommodated the potential problems that arise. For example, it is not clearly and concretely stated how to regulate campaigns using ‘video’ media in registered social media accounts. Furthermore, limiting the number of social media accounts to 20 is considered ineffective because it is easily circumvented by creating new unofficial accounts supported by buzzers. It also generalizes the regulation of election campaign advertisements in print mass media and online media, social media, and broadcasting institutions in the form of commercial and service advertisements for the community. Therefore, it is appropriate to add the diction of the word ‘video’ in Article 37 paragraph (4) and also regulate the technicalities of accounts other than official accounts deliberately created to benefit the campaign of election participants by adding new norms in PKPU.